PENGARUH KEPUASAN KARYAWAN PADA KOMPENSASI LANGSUNG,KOMPENSASI TIDAK LANGSUNG, PEKERJAAN, DAN LINGKUNGAN PEKERJAAN TERHADAP TURNOVER INTENTION - Yovita Veronika Selanno; Patrick Vivid Adinata; Ferrynela Purbo Laksono (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2019)
Turnover is a painful issue in the organizations, in the world of tough competition the organizations try to minimize their turnover ratio and save their cost, turnover cost consists of hiring, recruiting and selecting the employees. The study aimed to find out the influence of satisfaction of RS Emanuels nurse on the direct compensation, indirect compensation, job, and environment work toward turnover intention. The data were collected from 100 respondents of 220 nurses by using a structure questionnaire. By using multiple linier Regression, this study revealed that the employees satisfaction on direct compensation, indirect compensation, job, and environment work affected simultaneously and partially turnover intention.